Estratégia de produção em microempresas de marcenaria - Guerreiro, Érico Daniel Ricardi (2012)
Apparently, the small wood furniture factories have an outdated organization of production, however, they are active in the market for quite some time. In order to understand how the manufacturing strategy of small wood furniture factories helps these companies to stay in the market, this paper studies the content of manufacturing strategy, its alignment with the competitive strategy and with the production system. A research methodology combined a cross-sectional exploratory survey with 40 companies and a multiple case research in three companies. It was observed that the manufacturing strategy adopted is aligned with the competitive strategy of companies. It was observed also that the production system is suitable for manufacturing strategy, but results in some incompatibility with the delivery performance and cost. The main limitation of this study is the geographic concentration of companies participants.